Emerging Role of Secondary Bystander Effects Induced by Fractionated Proton Microbeam Radiation - Narongchai Autsavapromporn (2019)
© 2019 by Radiation Research Society. All rights of reproduction in any form reserved. Increased understanding of radiation-induced secondary bystander effect (RISBE) is relevant to radiation therapy since it likely contributes to normal tissue injury and tumor recurrence, subsequently resulting in treatment failure. In this work, we developed a simple method based on proton microbeam radiation and a transwell insert co-culture system to elucidate the RISBE between irradiated human lung cancer cells and nonirradiated human normal cells. A549 lung cancer cells received a single dose or fractionated doses of proton microbeam radiation to generate the primary bystander cells. These cells were then seeded on the top of the insert with secondary bystander WI-38 normal cells growing underneath in the presence or absence of gap junction intercellular communication (GJIC) inhibitor, 18-α-glycyrrhetnic acid (AGA). Cells were co-cultured before harvesting and assayed for micronuclei formation. The results of this work showed that fractionated doses of protons caused less DNA damage in the secondary bystander WI-38 cells compared to a single radiation dose, where the means differ by 20%. However, the damaging effect in the secondary bystander normal cells could be eliminated when treated with AGA. This novel work reflects our effort to demonstrate that GJIC plays a major role in the RISBE generated from the primary bystander cancer cells.